Aplicação de biofungicidas no controle do fungo Aspergillus flavus L. em amendoim (Arachis hypogaea) - Gorayeb, Teresa Cristina Castilho [UNESP] (2015)
This study aims to evaluate the technical feasibility of the application of biofungicides extracted from plants in the processing of peanut (Arachis hypogaea L.), with the objective of reducing infestation by fungus Aspergillus flavus L., and consequent contamination by aflatoxin, a chemical hazard. Firstly, we studied the fungal and aflatoxin contamination for the 2011/12, 2012/13, and 2013/14 crops, during the Runner IAC 886 peanut pods' harvesting and post-harvesting stages, in the region of Jaboticabal, Sao Paulo, Brazil, and proposed the Hazard Analysis and Critical Control Points (HACCP). The results of the pods' humidity showed a decrease, on average, of 65.65% d.b. on uprooting, to 7.17% d.b. on storage, and the fungal contamination was higher for 2013/2014 crops; the aflatoxin levels were below the required by current legislation. HACCP showed the control points (CP) during uprooting, sun drying, mechanical harvesting, and transportation; and the PCCs during stages of reception, drying, and storage proved the best stage for biofungicide application is before artificial drying. The second stage consisted of obtaining biofungicides as aqueous, alcoholic, and essential oil extracts from the plants: cinnamon (Cinnamomum zeylanicum), cloves (Syzygium aromaticum), lemon grass (Cymbopogon citratus), oregano (Origanum vulgare), and basil (Ocimum basilicum); then, we evaluated those in inhibiting the fungus Aspergillus flavus L. and synthesizing aflatoxin. The biofungicides' inhibiting efficiency on Aspergillus flavus L. was evaluated in Potato Dextrose Agar medium (PDA), by mycelial growth inhibition technique (MGI), by minimum inhibitory concentration (MIC), and by applying the most efficient oils on the contaminated peanut pods, stored in controlled humidity and room temperature, thus determining colony-forming units (CFU/g) and aflatoxins. The extracts' MGI results showed that there was no...